The Effects of Regional Own-Source Revenue and General Allocation Fund on Economic Growth: Evidence from Spatial Panel Regression in North Kalimantan Province, Indonesia - Asih Kusuma Wijayanti; Anwar Anwar; Budi Hasyim (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study examines variations in Regional Own-Source Revenue (PAD), the General Allocation Fund (DAU), and economic growth across North Kalimantan’s five local governments during 2014–2023. Research Method: The study uses an observational panel-data design based on 50 local-government-year observations obtained from Statistics Indonesia and the Directorate General of Fiscal Balance. Descriptive analysis and the Pesaran cross-sectional dependence test were applied. Spatial panel estimation was excluded because the five-unit cross-sectional dimension was insufficient for stable spatial parameters and the original weights matrix could not be reproduced. Results and Discussion: Economic growth and fiscal capacity varied substantially across jurisdictions and years. The Pesaran CD statistic was 9.215 (p<0.001), indicating general residual dependence, but not geographically structured spatial dependence. Accordingly, no reliable spatial or causal conclusion regarding PAD and DAU was retained. Implications: Fiscal policy should consider regional heterogeneity, revenue composition, transfer dependence, and common economic shocks. Broader samples and explicit endogeneity strategies are required for confirmatory analysis. Originality: The study provides context-specific fiscal evidence from Indonesia’s newest border province while clarifying the distinction between cross-sectional and spatial dependence.